Has the Euro affected the choice of invoicing currency? - Jenny E. Ligthart; Sebastian E. V. Werner (European Central Bank (ECB), 2012)
We present a new approach to study empirically the effect of the introduction of the euro on the pattern of currency invoicing. Our approach uses a compositional multinomial logit model, in which currency choice is explained by both currency-specific and country-specific determinants. We use unique quarterly panel data on the invoicing of Norwegian imports from OECD countries for the 1996-2006 period. We find that eurozone countries have substantially increased their share of home currency invoicing after the introduction of the euro, whereas the home currency share of non-eurozone countries fell slightly. In addition, the euro as a vehicle currency has overtaken the role of the US dollar in Norwegian imports. The substantial rise in producer currency invoicing by eurozone countries is primarily caused by a drop in inflation volatility and can only to a small extent be explained by an unobserved euro effect.
Keywords: F33; F41; F42; E31; C25; 330; compositional multinomial logit; euro; exchange rate risk; inflation volatility; invoicing currency; vehicle currencies